Bosporus Bridge toll plaza in Istanbul, Turkey - Upstream and downstream traffic features - Sahin, I; Akyildiz, G (TRANSPORTATION RESEARCH BOARD NATL RESEARCH COUNCIL, 2005)
The Bosporus Bridge in Istanbul, Turkey, is the first of the two highway crossings connecting Asia and Europe over the Bosporus Strait. Drivers must pay their toll in the Europe-to-Asia direction at a toll plaza comprising 15 lanes. Manual and electronic payment methods are available in the plaza. The analysis of data showed that several factors affect both the throughput of the plaza and the traffic flows approaching it. Among the factors were whether a particular toll lane was in service, the contraflow lane operation toward the plaza, the lane operators' performance, and the queue lengths in the plaza area. Rescaled cumulative vehicle count curves were used as the analysis tool. This allowed observation of (a) flow changes at particular points along the section of the highway studied and (b) propagation of the kinematic waves upstream of the plaza. The observations could be used for improving the performance of the plaza and for traffic management decisions associated with the afternoon peak period.
Keywords: Engineering; Transportation